Mining expansion and social protest in Argentina and Peru - Álvarez Huwiler, Laura (2015)
In Latin America in recent decades it has experienced significant growth and expansion of metal mining. This phenomenon has been generated by a number of factors, among which highlights the changes in legal frameworks. From this, the present article analyzes the process of mining expansion in two countries of the region, Argentina and Peru, with special attention to the related between mining expansion and social protest. A comparative growth of the mining sector in both countries, focusing on indicators of production, investment and export analysis is presented. Then, the most significant legal changes implemented in the mining sector are described. Finally, socio-environmental protests are analyzed, proposing some reflections about that. In conclusion we consider that both countries share some similarities regarding the expansion of metal mining, the orientation of their legal frameworks and the emergence of social protests. However, we highlight significant differences that we consider are related whit the importance of mining in the accumulation mode and what we call “mining traditions.”